Lithium exposure during pregnancy: outcomes for women who attended a specialist antenatal clinic - Jacqueline Frayne; Thinh Nguyen; Tabitha Mok; Yvonne Hauck; Helena Liira (Taylor & Francis Group, 2018)
Introduction: Lithium treatment in pregnancy represents a significant dilemma for women and treating health professionals alike. The complexity of risk-benefit analysis is impacted by limited information. Methods: A cohort study of 33 women with severe mental illness, who were prescribed lithium at any time during the pregnancy, and gave birth between December 2007 and January 2015 at a specialist antenatal clinic in Western Australia. A descriptive comparison for women who continued lithium throughout pregnancy, and those who ceased on discovery of pregnancy was undertaken examining demographic, obstetric, neonatal and psychiatric variables. Results: Women who were prescribed lithium, irrespective of whether they continued or discontinued the medication represented a high risk group obstetrically, with high rates of smoking overall (33%) medical comorbidities (54%) and antenatal complications (88%). Preconception counseling occurred in 33% of the cohort but increased the likelihood of continuing lithium in pregnancy (p = .007). Compared to those who ceased lithium, women who remained on lithium through the pregnancy had increased rates of fetal ultrasound abnormalities such as abdominal circumference >90th % (p = .005). Psychiatric relapses through the antenatal and immediate postpartum period appeared to be due to a combination of factors. Discussion: Pregnant women with severe mood disorders treated with lithium are a vulnerable, high-risk obstetric population who would benefit from preconception counseling, regular antenatal care in a tertiary center, delivery with neonatal pediatric support and experienced psychiatric management.